2020
DOI: 10.1183/13993003.02537-2020
|View full text |Cite
|
Sign up to set email alerts
|

Solitary pulmonary nodule imaging approaches and the role of optical fibre-based technologies

Abstract: Solitary pulmonary nodules (SPNs) are a clinical challenge, given there is no single clinical sign or radiological feature that definitively identifies a benign from a malignant SPN. The early detection of lung cancer has a huge impact on survival outcome. Consequently, there is great interest in the prompt diagnosis, and treatment of malignant SPNs. Current diagnostic pathways involve endobronchial/transthoracic tissue biopsies or radiological surveillance, which can be associated with suboptimal diagnostic y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 145 publications
(189 reference statements)
0
18
0
Order By: Relevance
“…Label free optical imaging modalities have the potential to characterize lung cancer using both optical endomicroscopy and fluorescence lifetime imaging (FLIM) systems ( 36 ). Here we used a clinically approved fluorescence and FLIM imaging system ( 31 ) which was compatible with bronchoscopy, where a fibre can be passed through the working channel to access tumours and lung parenchyma ( Supplementary Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Label free optical imaging modalities have the potential to characterize lung cancer using both optical endomicroscopy and fluorescence lifetime imaging (FLIM) systems ( 36 ). Here we used a clinically approved fluorescence and FLIM imaging system ( 31 ) which was compatible with bronchoscopy, where a fibre can be passed through the working channel to access tumours and lung parenchyma ( Supplementary Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…GGOs are the most challenging pulmonary lesions to evaluate during diagnostic biopsy because they are often early-stage adenocarcinoma spectrum lesions that have a soft tissue architecture not easily distinguishable from normal lung parenchyma [31]. GGOs, unlike solid nodules, cannot be seen using fluoroscopy and radial endobronchial ultrasound (r-EBUS), and no technique is available for real-time visualization of GGOs [3,32,33]. In all GGOs evaluated in this study, fluorescent cancer cells were identified within the lesion during biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing use of computed tomography scanning in medical practice and lung cancer screening guidelines has made it commonplace to detect pulmonary nodules radiographically suspicious for malignancy [1,2]. These solitary pulmonary nodules (SPNs)-spherical radiographic opacities less than 3 cm in diameter that are surrounded by normal lung-present a significant clinical challenge, as the majority are benign but a nontrivial portion represent early-stage, curable lung cancers [3]. There is no clinical or radiological feature that definitively identifies malignant SPNs, and SPNs often require endobronchial or transthoracic tissue biopsy to rule out malignancy [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical endomicroscopy, such as fibre-based confocal laser fluorescence endomicroscopy (CLE), is a high-resolution imaging technique, which enables autofluorescence visualisation of individual cells and structures of the respiratory tract and distal lung parenchyma at a near microscopic level. Probe-based confocal laser endomicroscopy (pCLE) is available since 2008 using a thin semiflexible 1.2 mm probe (Alveoflex, Cellvizio System; Mauna Kea Technologies, Paris, France), which is inserted through the working channel of a bronchoscope 7 8. It consists of 30 000 optical fibres enabling a lateral resolution of 3 µm, confocal depth of focus of 0–50 µm and a 600 µm field of view.…”
mentioning
confidence: 99%